2011
DOI: 10.1029/2011jd015899
|View full text |Cite
|
Sign up to set email alerts
|

Future climate change impacts on summer surface ozone from regional climate-air quality simulations over Europe

Abstract: [1] Regional climate-air quality simulations were performed over Europe for two future decades, 2041-2050 and 2091-2100 under IPCC A1B scenario and the control decade 1991-2000. The simulations serve as a theoretical experiment investigating the impact of changing climate on summer surface ozone. Our simulations suggest that changes in summer surface ozone imposed by climate change until the 2040s are below 1 ppbv and more pronounced until the 2090s. The median of summer near surface temperature for whole Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 73 publications
9
68
0
4
Order By: Relevance
“…Bloomer et al (2009) estimated the magnitude of these effects from surface ozone observations over the US at about 2.2 ppb per degree Celcius and Pfister et al (2014) showed increasing summertime ozone levels under various climate scenarios. These effects have been quantified over Europe in several model studies Meleux et al, 2007;Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013bKatragkou et al, 2011). The general order of magnitude of the climate penalty over Europe is a few ppb by the middle of the century.…”
Section: Hemispheric Transport Of Ozone and It Precursors In The Polimentioning
confidence: 99%
See 1 more Smart Citation
“…Bloomer et al (2009) estimated the magnitude of these effects from surface ozone observations over the US at about 2.2 ppb per degree Celcius and Pfister et al (2014) showed increasing summertime ozone levels under various climate scenarios. These effects have been quantified over Europe in several model studies Meleux et al, 2007;Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013bKatragkou et al, 2011). The general order of magnitude of the climate penalty over Europe is a few ppb by the middle of the century.…”
Section: Hemispheric Transport Of Ozone and It Precursors In The Polimentioning
confidence: 99%
“…Several other studies have focused only on the regional impact of climate change (Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013Katragkou et al, 2011). They found a general increase in ozone concentrations owing to increasing biogenic emissions and favourable conditions for the build-up of ozone pollution as a result of increased temperature, more frequent summer blocking and heat waves and increased short-wave radiation.…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%
“…A significant portion of the published literature on this issue uses global-scale models to focus on the impact of climate on tropospheric ozone at the global or regional scale (Brasseur et al, 1998;Liao et al, 2006;Prather et al, 2003;Szopa et al, 2006;Szopa and Hauglustaine, 2007). More recent studies have integrated advanced chemistry schemes capable of resolving the variability of pollutant concentrations at regional scale, which spans from several hours up to a few days, with chemistry transport models (CTMs) (Colette et al, 2012Knoche, 2006, 2007;Hogrefe et al, 2004;Katragkou et al, 2011;Kelly et al, 2012;Knowlton et al, 2004;Lam et al, 2011;Langner et al, 2005Langner et al, , 2012Nolte et al, 2008;Szopa and Hauglustaine, 2007;Tagaris et al, 2009;Zanis et al, 2011). Global models with a typical resolution of a few hundreds of kilometers and regional CTMs used at resolutions of a few tens of kilometers, and their parameterization of physical and chemical processes make them inadequate for modeling airquality at the urban scale (Cohan et al, 2006;Forkel and Knoche, 2007;Markakis et al, 2014;Sillman et al, 1990;Tie et al, 2010;Valari and Menut, 2008;Valin et al, 2011;Vautard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Langner et al, 2005;Knoche, 2006, 2007;Meleux et al, 2007;Giorgi and Meleux, 2007;Hedegaard et al, 2008;Andersson and Engardt, 2010;Katragkou et al, 2011). Model assessments of air quality responding to a changing future climate indicate that some parts of Europe are expected to typically be both warmer and have higher O 3 levels.…”
mentioning
confidence: 99%